2004
DOI: 10.1016/s0006-3495(04)74285-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Disaccharide Trehalose with a Phospholipid Bilayer: A Molecular Dynamics Study

Abstract: The disaccharide trehalose is well known for its bioprotective properties. Produced in large amounts during stress periods in the life of organisms able to survive potentially damaging conditions, trehalose plays its protective role by stabilizing biostructures such as proteins and lipid membranes. In this study, molecular dynamics simulations are used to investigate the interaction of trehalose with a phospholipid bilayer at atomistic resolution. Simulations of the bilayer in the absence and in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
124
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 80 publications
(118 reference statements)
30
124
1
4
Order By: Relevance
“…found very similar effects [24]. The area per molecule is almost unaffected even with 128 molecules of trehalose for 128 molecules of DPPC.…”
Section: Bilayer Structure and Influence Of Small Moleculesmentioning
confidence: 60%
See 1 more Smart Citation
“…found very similar effects [24]. The area per molecule is almost unaffected even with 128 molecules of trehalose for 128 molecules of DPPC.…”
Section: Bilayer Structure and Influence Of Small Moleculesmentioning
confidence: 60%
“…More recently computational studies of mixtures of various phospholipids [12,13,14,15] and of phospholipids with cholesterol [16,17,18,19] have also been reported. However, the question how such lipid bilayer membranes interact with small molecules has to date not gained very much attention except for a few initial studies on alcohols [20,21,22], sugars [23,24], and dimethylsulfoxide (DMSO) [25,26]. The influence of lipophilic polymers on lipid bilayers has also been studied [27].…”
Section: Introductionmentioning
confidence: 99%
“…It is found in organisms like insects, yeast and fungi; organisms that tend to accumulate trehalose under stressful conditions like anhydrobiosis, heat shock or osmotic stress to a greater degree than any other known sugars. Several studies have shown that trehalose could stabilize membranes and proteins under unfavourable conditions (Pereira et al 2004). Based on these characteristics, trehalose has been examined for its favourable effects on human cells and biostructures undergoing stress, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There are several molecular features that govern the behavior of a drug in cell membranes such as size, shape, solubility, hydrophilicity, lipophilicity, and pK a , among others. Previously, many authors have reported studies of the interaction of drugs and membrane models with experimental technics (Nunes et al 2011;Lucio et al 2009;Fuchs et al 1990) and molecular dynamic (MD) simulations (Robinson et al 1995;Gabdouline et al 1996;Smondyrev andBerkowitz 1999, 2001;Hofsäß et al 2003;Pereira et al 2004;Falck et al 2006;Högberg et al 2007;Seddon et al 2009;Sirk et al 2009;Boggara and Krishnamoorti 2010;Witzke et al 2010;Orsi andEssex 2010, Koukoulitsa et al 2011;Nitschke et al 2012;Poger and Mark 2013;Loverde 2014;Jalili and Saeedi 2016). In particular, studies based on drug partitioning in lipid bilayers and the thermodynamics of drug/lipid interaction have great importance in understanding the reaction mechanisms of antitumor drugs and to design new cell membrane-targeted drugs (Boggara and Krishnamoorti 2010;Jendrossek and Handrick 2003;Goldstein et al 2011;Choi et al 2013).…”
Section: Introductionmentioning
confidence: 99%